2022
DOI: 10.1097/bot.0000000000002293
|View full text |Cite
|
Sign up to set email alerts
|

Open Ankle Fractures: What Predicts Infection? A Multicenter Study

Abstract: Objective: To identify the patient, injury, and treatment factors associated with an acute infection during the treatment of open ankle fractures in a large multicenter retrospective review. To evaluate the effect of infectious complications on the rates of nonunion, malunion, and loss of reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Overall, we found a 2.2% incidence of confirmed FRI, which is consistent with the reported prevalence of surgical site infections in the United States. 1,2,[7][8][9] In this study, we identified social risk factors that were associated with the development of FRI after fracture surgery. Our data suggest that Black and Hispanic populations are more likely to develop FRI after fracture fixation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, we found a 2.2% incidence of confirmed FRI, which is consistent with the reported prevalence of surgical site infections in the United States. 1,2,[7][8][9] In this study, we identified social risk factors that were associated with the development of FRI after fracture surgery. Our data suggest that Black and Hispanic populations are more likely to develop FRI after fracture fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we found a 2.2% incidence of confirmed FRI, which is consistent with the reported prevalence of surgical site infections in the United States. 1,2,7–9…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Additional studies have identified predictors of poor outcomes following ankle fractures including increased age, body mass index (BMI) >30, high American Society of Anesthesiologists score, male sex, smoking status, history of diabetes, immunosuppressant use, severity of fracture, and time to wound closure. 7,8,13,18,29,31 Although studies have shown the impact of CKD and the associated bone disturbance on outcomes associated with other traumatic fractures, there is a scarcity of literature describing the effect of CKD on outcomes of ankle fractures. This study will examine the impact of CKD on clinical outcomes following torsional ankle fracture, including complications and unplanned surgical procedures.…”
Section: Introductionmentioning
confidence: 99%